Testing the Representational Deficit Hypothesis: From the Aspect of Chinese Learners’ Acquisition of Affixation ‘-s’ for Third Person Singular Verbs and Plural Nouns - Li, Ni; Yang, Lianrui (Frontiers in Psychology, 2022)
The persistent difficulty in making verbal inflections is commonly recognized for second language learners, especially for Chinese speaking students. researchers put forward different hypotheses to explain the problems in acquiring inflectional morphology. Among them, the representational deficit hypothesis deficit(RDH), advocated by Hawkins and Liszka (2003), indicates that adult learners will fail to make inflectional morphology to interpret the corresponding syntactic feature if there is no counterpart system in their native language. In English, affix morpheme ‘-s’ marks either third person singular (3SG) or regular plural nouns. In contrast, Chinese is a language which lacks 3SG markings but presents the morpheme ‘men’ to reflect a plural feature for nouns with a human property. To test the applicability of the RDH in the domain of affix ‘-s’ for English learners of Chinese, the present study observed the morphological inflections of the third person singular and plural '-s' in 33 Chinese EFL learners' written and spoken production tasks. The results show that the participants distinguished between the inflectional morphology in regular plural and 3SG thematic verb markings, which was compatible with the RDH. Additionally, other phenomena related to 3SG and plural morphological inflections provided strands of evidence for the RDH, for instance, L2 exposure age, a prominent overuse of plural ‘-s’, and exceptional cases for more 3SG ‘-s’ markings in the written data. Except for the account of morphosyntactic processes in the RDH, other factors, such as input frequency, difficulty of paradigm uniformity, and acquisition order were referred to as the way that the L2 learners’ acquisition of the morphological inflections was affected.